Factor influencing job satisfaction among nurses' in Hospital Sultan Abdul Halim / Nur Farah Hana Abdul Kadir and Syafiqah Nabila Shaari - Abdul Kadir, Nur Farah Hana; Shaari, Syafiqah Nabila (2018)
This research was conducted to study the factors that influencing job satisfaction among nurses' in Hospital Sultan Abdul Halim. This study conducted in order to determine which factors need to be highlight by Hospital Sultan Abdul Halim to ensure that their staffs have a high level of job satisfaction and to ensure the lower level of turnover and intention to leave from their current job. In this study the quantitative research method had been used in which relies on the primary data from survey which involve the nurses' in Hospital Sultan Abdul Halim. The total sample size for this study is 260 respondents. This study had conducted on this amount of sample sizes and the data had been collected in second week on November 2018. The analysis on the findings for these studies have managed to answer all objective stated. From the findings, the researcher had found out there is relationship between job satisfaction with all the independent variables such as work environment, workloads and teamwork. Therefore, it could be concluded that there was relationship between job satisfactions among nurses' in Hospital Sultan Abdul Halim with all of the variables.